Tamale City in Ghana is making use of climate change vulnerability assessments and applying the City Region Food Systems toolkit to strengthen food security - CGIAR Research Program on Water, Land and Ecosystems (2021)
WLE supported the RUAF-FAO City Region Food Systems (CRFS) program to develop an approach and toolkit to assess food system vulnerability. WLE/IWMI and RUAF have been working with the Tamale Metropolitan Assembly (TaMA) in Ghana to develop the CRFS tool and enhance understanding of the tool by multiple stakeholders for action planning. This has led to the formation of a core group and multi-stakeholder platform to support development of action plans to address food system challenges.